Modeling Hospital Information Systems (Part 2): Using the 3LGM2 Tool for Modeling Patient Record Management - Wendt, T.; Häber, A.; Brigl, B.; Winter, A. (Methods of Information in Medicine, 2004)
Objectives: We introduce the 3LGM2 tool, a tool for modeling information systems, and describe the process of modeling parts of the hospital information system of the Leipzig University Hospital (UKLa). We modeled the sub information systems of five patient record archiving sections to support the creation of a proposal for governmental financial support for a new document management and archiving system. We explain the steps of identifying the model elements and their relations as well as the analyzing capabilities of the 3LGM2 tool to answer questions about the information system.Methods: The 3LGM2 tool was developed on the basis of the meta model 3LGM2 which is described in detail in [1]. 3LGM2 defines an ontological basis, divided into three layers and their relationships. In addition to usual meta CASE tools, the 3LGM2 tool meets certain requirements of information management in hospitals. The model described in this article was created on the base of on-site surveys in five archiving sections of the UKL.Results: A prototype of the 3LGM2 tool is available and is currently tested in some projects at the UKL and partner institutions. The model presented in this article is a structured documentation about the current state of patient record archiving at the UKL. The analyzing capabilities of the 3LGM2 tool help to use the model and to answer questions about the information system.Conclusions: The 3LGM2 tool can be used to model and analyze information systems. The presentation capabilities and the reliability of the prototype have to be improved. The initial modeling effort of an institution is only valuable if the model is maintained regularly and reused in other projects. Reference catalogues and reference models are needed to decrease this effort and to support the creation of comparable models.
Keywords: Information management; hospital information systems; models (theoretical); information management; organizational model; 3LGM2; computerized models; documentation; patient record